Immunometabolic regulation of disulfidptosis in orthopedic diseases: mechanistic heterogeneity and therapeutic targets - Zhao, Xiaoming; Zhang, Chen; Qu, Lian; Gao, Jun; Wu, Shaobo; Zhang, Yilei; Zhang, Yingang (Frontiers in Immunology, 2025)
Disulfidptosis is a novel form of programmed cell death triggered by cystine metabolic disorders and disulfide stress, initially studied primarily in the context of tumors. In recent years, its role in the occurrence and development of orthopedic diseases has gained increasing attention. This review systematically explores the dual regulatory mechanisms of disulfidptosis in degenerative orthopedic diseases, such as intervertebral disc degeneration, osteoporosis, and osteoarthritis, as well as in malignant bone tumors like osteosarcoma, along with their immunometabolic basis. The research findings indicate that in degenerative lesions, microenvironmental stresses such as ischemia and hypoxia exacerbate tissue degeneration by promoting abnormal accumulation of disulfide bonds and damaging the cytoskeleton. In osteosarcoma, tumor-associated oxidative stress can induce metabolism-dependent cell death, providing new opportunities for targeted therapy. The article further summarizes key signaling pathways and molecular regulatory networks, discussing the potential value of targeted intervention strategies in slowing disease progression and achieving precision treatment.